2017
DOI: 10.15376/biores.12.1.1201-1215
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Cellulose to 5-Hydroxymethylfurfural using Inorganic Acidic Catalysts in the Presence of Pressurized Water Steam

Abstract: Traditionally, 5-hydroxymethylfurfural (HMF) is produced by using a waterorganic solvent medium, which inevitably increases production costs and adds subsequent separation processes. To minimize cost and/or toxic organic solvent usage, this study presents an effective pathway for producing HMF from cellulose. The process uses a fixed bed reactor with a steam stripping process in which the cellulose is converted into HMF and other products in the presence of acidic inorganic salts. In the process, the cellulose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
(27 reference statements)
1
5
0
Order By: Relevance
“…Some studies in the literature [37][38][39][40][41][42][43][44][45] have reported works with HMF and FF yields close to those found in this work using different residual biomass as raw material. Zhang et al 21 reported the production of HMF and FF from maize ear with yields of about 66% (after 65 min reaction) and 10% (after 85 min reaction), respectively, at 175 °C.…”
Section: Ftir Spectroscopysupporting
confidence: 78%
See 1 more Smart Citation
“…Some studies in the literature [37][38][39][40][41][42][43][44][45] have reported works with HMF and FF yields close to those found in this work using different residual biomass as raw material. Zhang et al 21 reported the production of HMF and FF from maize ear with yields of about 66% (after 65 min reaction) and 10% (after 85 min reaction), respectively, at 175 °C.…”
Section: Ftir Spectroscopysupporting
confidence: 78%
“…The yields of these compounds were calculated using the equations 3 and 4 proposed by Cai et al: 39 (3) (4)…”
Section: High Performance Liquid Chromatography (Hplc) Analysismentioning
confidence: 99%
“…Compound concentrations were calculated based on calibration curves generated from the standard solutions; subsequently, they were applied according to equations 3 and 4. 17 (3) 4Higher heating value (HHV)…”
Section: Furanic Contentsmentioning
confidence: 99%
“…Thus, more efforts have been addressed to their conversion into valuable products, under the perspective of “bio-refinery”. In particular, 5-hydroxymethyl-2-furaldehyde (HMF) is one of the most promising renewable products. It has a very reactive structure due to the presence of the aldehydic and the hydroxyl groups and the furan ring, making it a key platform molecule for the synthesis of chemicals, biofuels, solvents and monomers. HMF is obtained by the acid-catalyzed dehydration of C6 fraction of biomass, including monosaccharides, such as glucose and fructose, and more complex polysaccharides, such as cellulose, starch and inulin. The monosaccharides are the ideal substrates for the HMF synthesis. In particular, fructose is the best HMF precursor because it can be directly converted into this furan compound through the loss of three water molecules .…”
Section: Introductionmentioning
confidence: 99%